Latitudinal Factor in the Cooling Process of Coastal Waters in the Eastern Part of the Baltic Sea - Korobchenkova Ksenia; Kileso Aleksandr; Kupriyanova Anastasia (Russian Journal of Earth Sciences, 2025)
A study of the latitudinal variation of the water cooling process along the eastern coast of the Baltic Sea in 2016 and 2018 was carried out based on field and reanalysis data. The latitudinal features of the anomalous cooling regime, previously noted off the coast of the Curonian Spit (Kaliningrad oblast, Russian Federation), were shown. Estimates of trends in decreasing coastal water temperatures were obtained for typical and anomalous cooling regimes. The role of a water temperature of 9.5 ∘C on the cooling rate of coastal waters is shown. Reaching this temperature from northeast to southwest occurs with a delay of about a month.